Morphogenesis, Estimated Allele Frequency, and Heterozygosity in The Putative Mutation Population of Solomon Teak (M1V1) - Ahmad Parlaongan,; Supriyanto,; Arum Sekar Wulandari,; Arin, (Journal of Sylva Indonesiana, 2025)
In vitro continuous development (proliferation) and growth enhancement of callus, which orginated from irradiated-plantlets of Solomon teak clones, have been sequentially conducted on culture medium of (1) MS + 0.1 ppm kinetin, then transferred to (2) an half-strength MS + 0.1 ppm kinetin + 0.1 ppm BAP + 100 ppm charcoal, to (3) an half-strength MS + 0.1 ppm BAP + 3% sugar and finally to (4) half strength MS + 0.3 ppm BAP + 3% sugar. The objectives of this research were to evaluate the morphogenesis of putative-mutant Solomon teak from generation M1V1 and estimate allele frequencies as well as population heterozygosity in vitro. Results demonstrated that exposure to gamma irradiation (10, 20, 30, and 40 Gy) in the M1V1 generation induced callus formation within two weeks, followed by the development of embryogenic callus. Genetic analysis revealed low diversity among M1V1 individuals as indicated by Na>Ne and He<Uhe. Gamma irradiation potentially increased both allele number and heterozygosity by approximately 50%. Ten putative-mutant teak seedlings are obtained, these lines should be maintained and propagated as valuable genetic resource for future teak improvement programs